Pembelajaran untuk Anak Tunarungu, Studi Kasus di SLB Karya Murni Ruteng, NTT - Ambros Leonangung Edu; Izul Islamudi; Asep Supena; Totok Bintoro (JIMAD: Jurnal Ilmiah Mutiara Pendidikan, 2025)
This study aims to understand the teaching methods, challenges, and character education for deaf children at SLB Karya Murni Ruteng, NTT. Using a qualitative approach with a case study design, the research involved interviews, observations, and documentation with the school principal, a second-grade teacher, and deaf students. Deaf children face significant challenges in verbal and social communication, requiring specialized teaching methods focusing on direct experiences, sign language, and intensive training such as “language immersion.” SLB Karya Murni implements contextual methods linking instructional materials to daily life, such as tactile exercises to enhance sensory perception and integrated speech training to strengthen vocal abilities. Additionally, conversation visualization programs are employed to help children understand and develop vocabulary. The study found that the learning process demands patience, creativity, and technological support to improve the cognitive and communication skills of deaf children. The school also emphasizes practical skill development through activities like woodworking and beauty salon workshops, preparing students for independent living. This research highlights the importance of inclusion-based character education, family involvement, and a supportive social environment, which are expected to enhance the active participation of deaf children in their communities. These findings are anticipated to serve as a reference for developing more effective and inclusive learning programs in other special education schools.